APPLICATION OF TECHNOLOGY-BASED FLIPPED LEARNING WITH A PROJECT-BASED LEARNING APPROACH: A CASE STUDY IN THE D3 JAPANESE STUDY PROGRAM OF TAKUMI POLYTECHNIC - Aldilah Alifany Darrienda (Sean Institute, 2023)
The development of contemporary technology, which prioritizes technology and digitalization, is also applied thoroughly in the Takumi Polytechnic environment, including during learning. As a vocational college that must equip its graduates with certain skills, learning at Takumi Polytechnic is project-based learning with the aim that students have mastered skills and even created something during their studies at Takumi Polytechnic. Opening the Regular Class and the Employee Class in the D3 Japanese Study Program at Takumi Polytechnic is a challenge because there are differences in study time in the two classes but the weight of the material and Graduate Learning Outcomes (CPL) are the same. This problem is tried to be solved by applying flip learning with the hope that students in the Employee Class can prepare material in advance before carrying out face-to-face lectures in class so that the difference in the length of learning time can be resolved. Research on the application of technology-based flip learning with a project-based learning approach in the D3 Japanese Study Program at Takumi Polytechnic was conducted to find the best learning path. This research was written as an evaluation of the implementation of learning using the technology-based flip learning method with a project-based learning approach in the D3 Japanese Language study program at the Takumi Polytechnic in the first semester of the 2022/2023 entry year.